Applying Quran Security and Hamming CodesFor Preventing of Text Modification (Baghdad Science Journal, 2011)
The widespread of internet allover the world, in addition to the increasing of the huge number of users that they exchanged important information over it highlights the need for a new methods to protect these important information from intruders' corruption or modification.This paper suggests a new method that ensures that the texts of a given document cannot be modified by the intruders.This method mainly consists of mixture of three steps. The first step which barrows some concepts of "Quran" security system to detect some type of change(s) occur in a given text. Where a key of each paragraph in the text is extracted from a group of letters in that paragraph which occur as multiply of a given prime number. This step cannot detect the changes in the reordering letters or words of the paragraph and text without changing the letters themselves. So, the next step uses one of the error detection methods which is named Hamming Codes to find out the locations of the change in the received text. After that; at the third step, RSA as a primary encryption method has been used to encrypt the keys extracted to the first step and second step in order to prevent the intruders to break down the security of the method.